Exploring the Nutritional, Medicinal and Economic Significance of Morchella Esculenta: a Comprehensive Review - Goutam, Nishant; Kumari, Shavinder; Garg, Shubham; Khuv Raj; Joshi, Gaurav (Scripta Medica, 2026)
This overview summarises the nutritional profile, medicinal properties, economic significance and traditional uses of Morchella esculenta (Guchhi). It also highlights research gaps to guide future studies. Information from multiple sources was synthesised to explore the mushroom’s nutritional composition, bioactive compounds, pharmacological activities, ethnobotanical relevance and economic role. M esculenta provides proteins, fibre and micronutrients such as zinc, selenium and iron, which contribute to immune support, antioxidant defence and blood health. Its pharmacological potential includes antioxidant, antitumour, antimicrobial and anti-inflammatory effects, largely attributed to polysaccharides (β-glucans, galactomannan) and phenolic compounds. Traditional uses for arthritis, fatigue and gastrointestinal disorders align with modern pharmacological findings. Economically, it remains one of the world’s most valuable wild fungi, supporting rural livelihoods. M esculenta is a nutritionally and pharmacologically significant mushroom with cultural and economic value. Further toxicological studies, clinical trials and cultivation research are needed to realise its full potential.
Keywords: Morchella esculenta; Phytotherapy; Toxicological phenomena; Nutrition assessment